+0  
 
0
205
1
avatar
Use the zero product property to solve each equation
1. t(t+1)=0
2.-3n(2n-5)=o
Guest Mar 15, 2012
 #1
avatar
0
t(t+1)=0
divide both sides by (t)

0/t = 0

t+1=0
subtract (1) from both sides
t=-1


* there is another way to complete this problem but the above example uses the zero product property

-3n(2n-5)=0
divide both sides by (-3n)

0/-3n = 0

2n-5=0
add (5) to both sides

2n = 5
divide both sides by (2)

n= 5/2 or 2.5
Guest Mar 16, 2012

14 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.